2016
DOI: 10.1002/humu.23130
|View full text |Cite
|
Sign up to set email alerts
|

Mutation inSSUH2Causes Autosomal-Dominant Dentin Dysplasia Type I

Abstract: Dentin dysplasia type I (DDI) is an autosomal-dominant genetic disorder resulting from dentin defects. The molecular basis of DDI remains unclear. DDI exhibits unique characteristics with phenotypes featuring obliteration of pulp chambers and diminutive root, thus providing a useful model for understanding the genetics of tooth formation. Using a large Chinese family with 14 DDI patients, we mapped the gene locus responsible for DDI to 3p26.1-3p24.3 and further identified a missense mutation, c.353C>A (p.P118Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…39 Recent genetic studies have shown that mutations of collagen type I alpha 1 chain ( COL1A1 ), collagen type I alpha 2 chain ( COL1A2 ), DSPP , secreted modular calcium-binding protein 2 ( SMOC2 ), vacuolar protein sorting 4 homologue B ( VPS4B ), and ssu-2 homologue ( SSUH2 ) cause dentin disorders. 3949 AMBN can enhance reparative dentin formation, which confirms that this protein has an important role in odontoblast differentiation and dentinogenesis. 50 The enamel defects confirm the observations from mouse models and show that human AI is associated with disrupted Ambn function.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…39 Recent genetic studies have shown that mutations of collagen type I alpha 1 chain ( COL1A1 ), collagen type I alpha 2 chain ( COL1A2 ), DSPP , secreted modular calcium-binding protein 2 ( SMOC2 ), vacuolar protein sorting 4 homologue B ( VPS4B ), and ssu-2 homologue ( SSUH2 ) cause dentin disorders. 3949 AMBN can enhance reparative dentin formation, which confirms that this protein has an important role in odontoblast differentiation and dentinogenesis. 50 The enamel defects confirm the observations from mouse models and show that human AI is associated with disrupted Ambn function.…”
Section: Introductionsupporting
confidence: 52%
“…Radiologically, permanent teeth of DD-I have short roots with a crescent-shaped pulpal remnant parallel to the cemento-enamel junction in the permanent dentition and total pulpal obliteration in the dentition. 48,49 There are usually numerous periapical radiolucencies in non-carious teeth. 48,49 Compared with DD-I, the clinical crowns of affected teeth in our study had similar pulp and root phenotypes, especially the phenotype of periapical radiolucencies in non-carious teeth (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of scanning electron microscopy revealed a significantly reduced number of dentin tubules with smaller diameters (Figure a,b). In addition, we have found two mutant genes: VPS4B (Yang et al., ) in a family from northern China; and SSUH2 in a family from southern China (Xiong et al., ). Different mutations can result in the same disease which is highly suggestive evidence that the disease has genetic heterogeneity.…”
Section: Identification Of Pathogenic Genes In Ddmentioning
confidence: 98%
“…To identify essential transcription factors in dental development, specific primers with different junctions at the three mRNA spliceosomes were designed for RT‐PCR amplification. Only the transcript NM_015931.2 including a 1,803 base pair mRNA is highly expressed in human dental pulp stem cells and underjaw tissues (Xiong et al., ). This transcript corresponds to a putative chaperone protein (approximately 39 kDa), which is widely distributed (Reinartz et al., ).…”
Section: Functional and Pathogenic Mechanism Of These Genesmentioning
confidence: 99%